Analysis of the relationship between inflation and the tax revenue in Iraq for the period 1990-2010 (Journal of Accounting and Financial Studies ( JAFS ), 2014)
The Iraqi economy has suffered for a long period of inflation because of the Iraq war and the resolutions and the sanctions that were imposed on Iraq, this phenomenon overshadowed at various aspects of the economy including the tax revenue that the State seeks to optimize the total income for the budget, the research covers the years 1990-2010, these years have been divided according to the country's economic variables.The research  adopted on econometrics analysis that is based on the information and data available on topics and has been using statistical methods to test functions are formulated.Research concluded that rates of inflation and GDP impact is limited to direct taxation and indirect in current prices and constant prices, because the select types refer to the instructions and decisions of administrative more than is associated with the economic reality in the country and this supports the hypothesis research.Research recommended: Activate the role of tax funding helping achieve economic and social stability, and work to return the inheritance tax, agricultural tax and value added tax and review of tax legislation to make the tax tool linked to economic reality.